2022
DOI: 10.1039/d2en00322h
|View full text |Cite
|
Sign up to set email alerts
|

Motion-based phenol detection and degradation using 3D hierarchical AA-NiMn-CLDHs@HNTs-Ag nanomotors

Abstract: Dual-functional micro/nano motors that can sensitively detect and rapidly degrade organic pollutants show great application prospect in the field of environmental remediation. Here we demonstrate the first proof-of-concept of a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…4a). 46 The above investigations proved that the peroxidase-like activity of 1 was mainly derived from ˙OH, which is from the decomposition of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 76%
“…4a). 46 The above investigations proved that the peroxidase-like activity of 1 was mainly derived from ˙OH, which is from the decomposition of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 76%
“…Tests have shown that some micro/nanomotors have excellent stability and reusability. 55,65 In addition, the propulsive properties of the micro/nanomotors promote the practical application of the micro/nanomotors in environmental monitoring 66,67 and degradation 73,82,83 of environmental pollutants, which makes the micro/nanomotors pivotal for environmental applications.…”
Section: Discussionmentioning
confidence: 99%
“…For simultaneous detection and removal of phenol from wastewater, Xing et al investigated an innovative three-dimensional (3D) hierarchical ascorbic acid-functionalized nickel manganese (NiMn)–calcined layered double hydroxides (CLDHs)@HNTs–Ag nanomotor (AANiMn–CLDHs@HNTs–Ag). 65 The average length and diameter of the AA–NiMn–CLDHs@HNTs–Ag micro/nanomotor are 970 nm and 200 nm. Autonomous motion, peroxidase-like activity, hierarchical structures, and highly exposed active sites were combined to enable highly sensitive and selective phenol detection as well as rapid phenol removal.…”
Section: Applicationsmentioning
confidence: 99%
“…prepared AA-NiMn-CLDHs@HNTs-Ag nanomotors by assembling AgNPs and NiMn-CLDH nanosheets inside and outside the lumen of natural halloysite nanotubes (HNTs) using a layer-by-layer self-assembly technique, which was able to degrade 95.63% of phenol within 90 min (Xing et al, 2022). Magnetic material Au@Ni/rGO with a size less than 8 nm and core-shell nanostructure was successfully synthesized and exhibited peroxidase-like activity, exhibiting excellent performance in the photodegradation behavior of phenol, 2-chlorophenol and 2-nitrophenol (Darabdhara and Das, 2019).…”
Section: Introductionmentioning
confidence: 99%